Wild mammals of Wyoming and Yellowstone National Park - Buskirk, Steven (University of California Press, 2016)
"This book provides the scholar, conservationist, and interested lay reader with information on the state's 117 wild mammalian species from grizzly bears to pygmy shrews. It describes the history of mammalogy in Wyoming, the zoogeography of Wyoming mammals, and the prehistoric mammals of Wyoming. It also characterizes the habitats of Wyoming mammals and addresses the conservation and management of mammals in the region. Expanding beyond the traditional field guide, the author emphasizes taxonomic classification, geographic range, and conservation status for mammalian species. Introductory sections are provided for each order and family, and individual species accounts organize a wealth of data ranging from habitat associations to field measurements in an easy-to-use format. Featuring color species photos, continental and state-scale distribution maps, and a comprehensive bibliography with nearly 1,000 references"--Provided by publisher